Evaluating the applicability of the european voluntary sustainability reporting standards for agrifood small- medium-sized enterprises - Tugliani, Teresa; Guareschi, Marianna; Arfini, Filippo (Italian Review of Agricultural Economics, 2026)
Sustainability reporting is a corporate social responsibility tool that engages businesses in sustainable practices and enables them to communicate their impacts to stakeholders. In the Italian Agrifood sector, small and medium-sized enterprises (SMEs) have an important role in the value chain but often lack the resources and skills to properly report their sustainability impacts. This study evaluates the potential capacity of agrifood SMEs to comply with and apply the Voluntary Sustainability Reporting Standards for Non-listed SMEs (VSME), using the Global Reporting Initiative (GRI) framework as a proxy. Using content analysis, 16 sustainability reports by Italian agrifood SMEs are examined in terms of material topics, use and informative coverage of GRI standards, and their correspondence with VSME indicators. The results reveal that social and environmental GRI topics and indicators are more frequently disclosed by SMEs, while economic topics receive limited attention. Moreover, comparison between GRI use and VSME requests highlights the absence of some specific agrifood sector indicators (biodiversity, soil health, pesticide use, local community impact, and product quality). Furthermore, the value chain perspective is weak in the VSME guidelines and in SME reporting. In conclusion, the VSME framework represents a starting point that requires refinement and dialogue between stakeholders to better support SME reporting. This study provides empirical insight into the underexplored segment of the sustainability reporting of agrifood SMEs.